Hubungan Kelelahan Terhadap Kualitas Hidup Anak Dengan Kanker Yang Menjalani Pengobatan - Ambrella, Feny Julia; Utami, Agnita; Wisanti, Eka (Medica Hospitalia : Journal of Clinical Medicine, 2021)
BACKGROUND : Cancer is a disease that can affect all age groups, including children. Children who suffer from cancer, must undergo various treatments to be able to kill the cancer cells in their bodies. One of the side effects of treatment is fatigue which can disrupt the quality of life in children with cancer. OBJECTIVE: The aim of this study was to identify whether fatigue can affect the quality of life in children with cancer. METHOD : This type of research is descriptive correlation with cross sectional design. The sample in this study were 45 people aged 2-18 years at the Indonesian Cancer Child Love Foundation (YKAKI) Riau. The sampling technique used was accidental sampling. Fatigue and quality of life in children with cancer were measured using the PedsQoL Multidimensional Fatigue Scale and the PedsQoL Generic 4.0. Data analysis used the Spearman rank test. RESULT : The results showed that there was a relationship between fatigue and quality of life in children with cancer (p value = 0.031), and showed that the average fatigue score experienced by children with cancer who underwent treatment was 46.80 (the higher the fatigue score the less fatigue was felt), while the quality As many as 34 people (75.6%) of children with cancer have a disrupted quality of life. The results of this study are expected to be able to help improve the quality of life in children with cancer to reduce fatigue due to the treatment they are undergoing which can affect the quality of life in children CONCLUSION : There is a significant relationship between fatigue and quality of life in children with cancer on treatment